Labor unions, globalization, and mercantilism - Wolf-Heimo Grieben; Fuat Sener (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyze the growth and welfare effects of globalization in a dynamic Schumpeterian North-South product-cycle model. Economic growth is driven by R&D activities of Northern entrepreneurs. Top Northern production technologies are imitated by the South. In the North, there is wage bargaining between a labor union and firms, and a minimum wage rate exists. Unilateral Northern trade liberalization reduces the rate of innovation, increases Northern unemployment, and reduces both Northern and Southern per-capita welfare. The effects are reversed in the case of unilateral Southern trade liberalization. Hence, wage bargaining above a given minimum wage promotes mercantilist behavior of developed countries.
Keywords: F12; F43; J51; O31; O32; 330; globalization : product cycle; endogenous growth; labor unions; minimum wage; mercantilism